2022
DOI: 10.1002/ijc.34058
|View full text |Cite|
|
Sign up to set email alerts
|

Association between medical androgen deprivation therapy and long‐term cardiovascular disease and all‐cause mortality in nonmetastatic prostate cancer

Abstract: Studies have suggested that prostate cancer (PCa) patients receiving androgen deprivation therapy (ADT) are at increased risk of developing or exacerbating cardiovascular disease (CVD). We aimed to explore the association between ADT for PCa and subsequent CVD and all‐cause mortality in this nationwide, longitudinal study. We also evaluated the role of cardiovascular risk and ADT duration to determine effect modification. Norwegian registry data were used to identify patients with PCa from 2008‐18 and who rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…The preva-lence of several drugs was higher in CRC-survivors than in the cancer-free population ten years after diagnosis, especially drugs for gastric acid disorder and pain medications (29). Among non-metastatic prostate cancer patients hormonal treatment was associated with an increased risk of cardiovascular disease (CVD) events, especially in patients with some CVD risk factors present at the time of their diagnosis and longer duration of treatment (30). We also found higher allcause mortality among patients receiving hormonal therapy.…”
Section: Long-term Adverse Health Effects In Cancer Patients: Prescri...mentioning
confidence: 65%
See 1 more Smart Citation
“…The preva-lence of several drugs was higher in CRC-survivors than in the cancer-free population ten years after diagnosis, especially drugs for gastric acid disorder and pain medications (29). Among non-metastatic prostate cancer patients hormonal treatment was associated with an increased risk of cardiovascular disease (CVD) events, especially in patients with some CVD risk factors present at the time of their diagnosis and longer duration of treatment (30). We also found higher allcause mortality among patients receiving hormonal therapy.…”
Section: Long-term Adverse Health Effects In Cancer Patients: Prescri...mentioning
confidence: 65%
“…Studies on drug use in survivors of colorectal and prostate cancer have been published (29,30). The preva-lence of several drugs was higher in CRC-survivors than in the cancer-free population ten years after diagnosis, especially drugs for gastric acid disorder and pain medications (29).…”
Section: Long-term Adverse Health Effects In Cancer Patients: Prescri...mentioning
confidence: 99%
“…However, the use of gonadotropin-releasing hormone (or androgen blockers) as a pharmacological androgen deprivation therapy (ADT) is considered highly effective in cis-men experiencing metastatic prostate cancer. Numerous studies indicate that ADT used to treat cis-men with prostate cancer is associated with adverse cardiovascular events that can lead to significant morbidity, 58,59 along with increased incidence of coronary heart disease, myocardial infarction, and sudden cardiac death. 60 ADT in cis-men is also associated with increased body weight and fat mass and a decrease in lean mass, [61][62][63][64] insulin resistance, 65 glucose intolerance, 66 diabetes, 60,67 and changes in lipid profiles (increased total cholesterol, non-HDL cholesterol, and LDL cholesterol).…”
Section: Gaht To Reduce Biological Effects Of Androgens In Twmentioning
confidence: 99%
“…Therefore, how to prevent death from CVD in cancer survivors is a question worth exploring. Although several studies have addressed this field, they mainly focused on breast, colorectal, prostate, and other cancers[ 16 - 18 ], and studies focusing on CVD outcomes in HCC patients have not been reported.…”
Section: Introductionmentioning
confidence: 99%